Modeling the apparent and intrinsic viscoelastic relaxation of hydrating cement paste. (January 2015) - Li, X.; Grasley, Z.C.; Garboczi, E.J.; Bullard, J.W.
Abstract: Finite element procedures combined with microstructure development modeling are integrated to quantitatively predict the viscoelastic/viscoplastic relaxation of cement paste due to intrinsic calcium silicate hydrate viscoelasticity and microstructure evolution associated with the hydration process. The combined models are implemented in a computational routine to predict time-dependent stress and strain fields in cement paste. The model simulations suggest that inherent viscoelastic deformation caused by calcium silicate hydrate is not necessarily the primary mechanism leading to the overall early-age viscoelastic/viscoplastic behavior of cement paste. The effect of time-dependent dissolution of cement grains occurring during the hydration process is substantial and should be considered as a significant mechanism for the apparent viscoelasticity/viscoplasticity of cement paste.